The 30 Juz Al-Qur'an Memorization Program as a Competitive Advantage for Madrasahs : Program Hafalan Al-Qur'an 30 Juz sebagai Keunggulan Kompetitif Madrasah - Sucipto, Hadi; Haryanto, Budi (Universitas Muhammadiyah Sidoarjo, 2025)
General background: The rapid growth of educational institutions has led to increasing competition, pushing schools to develop unique competitive strategies to attract students. Specific background: MA Islam Terpadu Darul Fikri (DAFI) in Sidoarjo leverages a 30-juz Quran memorization program to gain a competitive advantage. Knowledge gap: While many institutions use competitive strategies, there is a lack of specific research detailing how a comprehensive Islamic memorization program, integrated with general education, is successfully implemented as a core institutional strategy. Aims: This study investigates how the 30-juz Quran memorization program functions as a competitive advantage for MA DAFI. Results: The findings indicate that MA DAFI effectively integrates general education, religious studies, and skills training under a